Supporting post-pandemic recovery: a qualitative study of the capabilities, opportunities and motivations to deliver oral health behaviour change messages to parents of young children in community settings - Joanna Goldthorpe; Lauren Kilbee; Iain Pretty; Sarah Cotterill; Jo Hart; Sarah Peters (BMC, 2024)
Abstract Background The COVID-19 pandemic exacerbated vulnerabilities and inequalities in children's oral health, and treatment activity virtually ceased during periods of lockdown. Primary care dentistry is still in the post-pandemic recovery phase, and it may be some years before normal service is resumed in NHS dentistry. However, opportunities to support the dental workforce through offering some preventative care in outreach settings may exist. This has the additional benefit of potentially reaching children who do not routinely see a dentist. The aim of this research was therefore to explore views around upskilling practitioners working in early years educational and care settings to support families of pre-school aged children to adopt and maintain preventative oral health behaviours. Methods Using the Capability, Opportunity and Motivation model of behaviour (COM-B) to structure our data collection and analysis, we conducted semi-structured interviews with 16 practitioners (dental and non-dental) and analysed the data using deductive framework analysis. Results The data were a good fit with the COM-B model, and further themes were developed within each construct, representing insights from the data. Conclusion Early years practitioners can reach vulnerable children who are not usually brought to see a dentist, and have the capability, opportunity and motivation to support the oral health behaviours of families of children in their care. Further research is needed to identify training needs (oral health and behaviour change knowledge and skills), acceptability to parents, and supporting dental practice teams to work in partnership with early years settings.